PERAN ORANG TUA DAN SIKAP MATERIALISME MEMPENGARUHI KEPUTUSAN MENABUNG GEN-Z: LITERASI KEUANGAN SEBAGAI VARIABEL INTERVENING - Faiza Aliyah; Gryson Kirshner Haloho; Zalfa Putri Xaviera; Riyadi Aprayuda (Pusat P2M Politeknik Negeri Batam, 2025)
This research aims to study the factors that influence gen-z's saving decisions, focusing on financial literacy, the role of parents, and materialism. The research respondents were 340 students majoring in Management and Business at Batam State Polytechnic. This research uses a quantitative approach which consists of several stages, such as data collection, data processing using SmartPLS 3, outer and inner tests, hypothesis testing, and drawing conclusions. The research results reveal the significant role of parents in shaping the financial literacy and saving decisions of Gen-Z. Financial literacy also has a positive and significant effect on gen-z's saving decisions. The interesting finding that the materialism variable, which was previously considered negative, has a positive influence on Gen-Z's saving decisions, highlights the complexity of financial behavior. This research provides an important theoretical contribution by applying the Theory of Planned Behavior (TPB) to financial literacy, the role of parents, and materialism in saving decisions. Practically, this research provides a clear view for gen- z and parents regarding the factors that influence saving decisions, with the hope that gen-z can develop positive and sustainable saving habits, providing a positive impact on their financial stability in the future.